1978
DOI: 10.1002/jgt.3190020110
|View full text |Cite
|
Sign up to set email alerts
|

On ramsey numbers for books

Abstract: For n = 1, 2, . . . , let 6, = K2+ K,,. We pose the problem of determining the Ramsey numbers r (&, B,) and demonstrate that in many cases critical colorings are available from known examples of strongly regular graphs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 8 publications
1
39
0
Order By: Relevance
“…Books have attracted considerable attention in Ramsey graph theory (see, e.g. [8], [4] and [6]). In particular, Erdős et al [3] proved that for every fixed k,…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Books have attracted considerable attention in Ramsey graph theory (see, e.g. [8], [4] and [6]). In particular, Erdős et al [3] proved that for every fixed k,…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Rousseau and Sheehan in [8] proved that r (B n ) ≤ 4n + 2, and observed that the Paley graphs imply r (B n ) = 4n + 2 whenever 4n + 1 is a prime power. Hence, r (B n ) = (4 + o (1)) n. It is reasonable investigate the structure of red-blue edge colorings of K (4−ε)n without monochromatic B n when ε tends to 0.…”
Section: Introductionmentioning
confidence: 99%
“…. These bipartite Ramsey numbers have been explored extensively in the last decade (see [2,3,4,5,6] [1,10]) in the last decade. However, not much papers have been published in this area except for paths and cycles versus some small classes of graphs.…”
Section: H Gmentioning
confidence: 99%
“…The book Ramsey number rðB m ; B n Þ is the smallest integer r such that either B m & G or B n & G for every graph G of order r. The study of Ramsey numbers for books was initiated in [7] and continued in [5]. The following results are known.…”
Section: Introductionmentioning
confidence: 96%